Two-dimensional echocardiographic measurements of the right coronary artery in healthy horses – a pilot study - Siwinska, Natalia (BMC Vet Res, 2019)
BACKGROUND: Precise understanding of the dimensions of the vascular lumina is essential for accurate interpretation of cardiac vessels imaging. To the authors’ best knowledge, this is the first study focusing on the ultrasound measurement of the right coronary artery (RCA) in the horse. The aim of this study was to determine both the ultrasonographic range of the normal diameter and lumen area of the RCA in horses and the influence of gender, age and level of training on the RCA dimensions. An additional aim of the study was to assess intra- and inter-observer repeatability of the collected measurements. METHODS: Thirty-six privately owned, healthy horses were included in the study. The internal lumen diameter and the area of the RCA were measured in the right parasternal long axis view in the 3rd intercostal space during systole and diastole. The results were compared between groups using the analysis of variance (ANOVA) and Student’s t-test. The correlation between the physiological parameters and the RCA was assessed using Pearson correlation coefficient. Student’s t-test was used to compare the results obtained by two researchers and from two scanners. RESULTS: The mean diameter of the RCA was 13.1 ± 1.5 mm in systole and 11.5 ± 1.3 mm in diastole, and the mean area was 1.3 ± 0.2 cm(2) and 1.1 ± 0.2 cm(2), respectively. There were no statistically significant measurement differences between geldings and mares. A positive correlation between body weight and RCA dimensions as well as height and RCA dimensions were seen. There was a negative correlation between the age and the RCA area. A statistically significant difference in the RCA area was seen between race and retired horses. Intra- and inter-observer agreement was strong with a few statistically significant differences. CONCLUSIONS: The age, size, and level of training may affect the ultrasound measurement of the RCA in horses. Non-invasive transthoracic echocardiography may be used to assess the size of the right coronary vessel in various types of horses.